RELATIONSHIP BETWEEN UTILIZATION OF SULPHUR AND VIRULENCE AMONG ISOLATES OF FUSARIUM SOLANI CAUSING WILT OF CAULIFLOWER - RAJENDRA SINGH, V. C. SAXENA AND (Indian Phytopathology, 2002)
The paper deals with study of sulphur utilization in-vitro by three isolates of Fusarium solani (Mart.) Sacc. causing wilt of cauliflower (Brassica oleracea var. botrytis L.) and differing in their virulence. Out of the eight sulphur sources tried, all the isolates of wilt causing organism utilized maximum amount of sulphur from L-methionine and minimum from sodium bisulphate. There was quite apparent correlation between amount of sulphur utilized by the Fusarium isolates and their relative virulence, i.e., highly virulent isolate utilized comparatively more sulphur than moderately and less virulent isolates. However, no definite correlation could be established between maximum sulphur utilization and growth of the pathogen.